2010
DOI: 10.1586/erc.09.143
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren/valsartan combination for the treatment of cardiovascular and renal diseases

Abstract: Chronic activation of the renin-angiotensin-aldosterone system (RAAS) plays a key role in the development of hypertension, and cardiac and renal diseases. RAAS inhibitors, such as angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs), improve cardiovascular and renal outcomes. However, studies have shown that residual morbidity and mortality remains high, despite current optimal treatment. More comprehensive control of the RAAS might provide additional reductions in morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Combination therapy with aliskiren/losartan or aliskiren monotherapy significantly reduced plasma aldosterone from baseline by 21% and 25%, respectively, after 9 months of treatment compared with a 5% increase with losartan monotherapy in the ALLAY study [90]. In the AVOID study; aliskiren administered with losartan reduced urinary aldosterone from baseline by 24%, compared to 4% reduction with placebo [92].…”
Section: Direct Renin Inhibitor/arb or Ace Inhibitor Combinationmentioning
confidence: 94%
“…Combination therapy with aliskiren/losartan or aliskiren monotherapy significantly reduced plasma aldosterone from baseline by 21% and 25%, respectively, after 9 months of treatment compared with a 5% increase with losartan monotherapy in the ALLAY study [90]. In the AVOID study; aliskiren administered with losartan reduced urinary aldosterone from baseline by 24%, compared to 4% reduction with placebo [92].…”
Section: Direct Renin Inhibitor/arb or Ace Inhibitor Combinationmentioning
confidence: 94%
“…By inhibiting the enzymatic conversion by renin of Agt to Ang I, DRIs inhibit the initial and rate-limiting step in the RAAS cascade, thus reducing the production of all downstream products derived from Agt [50,51]. Furthermore, in both clinical studies [52] and in experimental animals [14], aliskiren reduces plasma and/or urinary excretion of aldosterone. The role of aldosterone in endothelial dysfunction, inflammation, proteinuria and fibrosis is well known [30].…”
Section: Blockade Of the Raas In Ckdmentioning
confidence: 99%
“…In addition, a clinical study reported that aliskiren reduces plasma and urinary excretion of aldosterone and thus may provide additional renoprotective effects (74). This drug has been shown to be an effective antihypertensive agent and some studies have also evaluated aliskiren as a potential renoprotective agent in CKD using proteinuria as a surrogate marker of CKD progression (8, 75 -78).…”
Section: Ras Drugsmentioning
confidence: 99%